Geospatial Assessment of Channel Planform and Migration in the Lower Reach of River Gongola, Adamawa State, Nigeria - Ikusemoran, M.; Zemba, A. A.; Tukur, A. L. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
Channel migration is the process by which stream channels move and shape floodplains through time. The river channel of the lower reach of River Gongola between Kiri dam and the inlet to River Benue has been subjected to channel migration since the impoundment of Kiri reservoir in 1984. In this study, temporal changes in river channel parameters such as width, area, perimeter, sinuosity and channel bars, as well as the channel migration of the lower reach of River Gongola were assessed. Landsat MSS image of 1975 (nine years before the commissioning of Kiri reservior) and Google maps of 1975, 1984, 1989, 1999, 2009 and 2019 were aquired, processed and analyzed for the changes in channel parameters and migration in each of the six selected years. Overlay method in ArcGIS 10.5 sofware and appropriate formula were used to obtain the values of the channel parameters as well as that of channel migration. The result of the study reveals that all the channel parameters have been subjected to changes. The channel width was widest in 1975 when the dam was not constructed. The largest channel bars in 1989 recorded positive impact on the channel width, perimeter, length and sinuosity as all these parameters covered the highest land area in the same year. The sinuosity index ranged from 1.22 to 1.26 which fall within the “sinuous” class and hence, the channel is currently in sinuous stage. Areas covered by erosion were more prominent in the river channel than areas with deposition. The initial vertical incision before and shortly after the impoundment of the reservoir has changed to lateral erosion which leads to channel widening. It was recommended that geospatial techniques should be applied in the temporal monitoring of river channels for reliable and accurate data for monitoring of river channels.